ЭНЕРГИЯ ВЫХОДНОЙ ЦЕПИ ИСТОЧНИКА УСКОРЯЮЩЕГО НАПРЯЖЕНИЯ - Мартынов , В.В.; Лебедев , Б.Б. (Інститут електродинаміки НАН України, Київ, 2013)
Problems of stored energy in high-voltage circuit capasities of the acceleration voltage switching source of nonresonance type are considered. The interrelation between value of the ripple output voltage, load resistance, capacitance filter and leakage inductance of multiwinding transformer are figured. Analytical calculations for output parameters of high-frequency multisectional square-wave voltage converters based on ratio between number and parameters of sections are suggested. By the example of source with 60kV voltage and 15 kW power for electron beam welding installation is shown that on transformation frequency 20 kH and ripple less than 2% stored energy in output circuit does not exceed 7 J, hereof approximately half of it is stored energy in cable capacity. References 10, table 1, figures 6.